2016
DOI: 10.21577/0103-5053.20160260
|View full text |Cite
|
Sign up to set email alerts
|

Study of Reactions of Two Mannich Bases Derived of 4’-Hydroxychalcones with Glutathione by RP‑TLC, RP‑HPLC and RP‑HPLC‑ESI‑MS Analysis

Abstract: 4'-Hydroxychalcones have been reported to possess several beneficial biological effects. Several lines of evidence accumulated to demonstrate increased biological activities of the Mannich base derivatives of the parent 4'-hydroxychalcones. Bioactivities of chalcones and related α,β-unsaturated ketones are frequently associated with their reactivity with cellular thiols, such as GSH. For comparison of GSH reactivity, two bis Mannich bases of two 4'-hydroxychalcones were synthesized and reacted with GSH under n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Furthermore, Mannich derivatives of hydroxychalcones have been reported to have increased anti‐inflammatory activity . In our previous communication synthesis and reaction of 4′‐hydroxychalcone 1 and its bis ‐Mannich derivative 2 (Figure ) with reduced GSH have been reported . Reaction of the investigated chalcones with GSH led to formation of two diastereomeric adducts in each case.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Furthermore, Mannich derivatives of hydroxychalcones have been reported to have increased anti‐inflammatory activity . In our previous communication synthesis and reaction of 4′‐hydroxychalcone 1 and its bis ‐Mannich derivative 2 (Figure ) with reduced GSH have been reported . Reaction of the investigated chalcones with GSH led to formation of two diastereomeric adducts in each case.…”
Section: Introductionmentioning
confidence: 92%
“…Under strong acid conditions (pH 3.2), the reaction rates were found to be significantly lower than those observed under more basic conditions (pH 6.1, pH 7.4, and pH 8.0). Furthermore, at each investigated pH, the rate of reaction of the bis ‐Mannich derivative 2 was found to be substantially higher than that of the parent (non‐Mannich) chalcone 1 …”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Reduced glutathione (GSH) is the most abundant cytosolic thiol playing important role in protection of cells against electrophiles-initiated damages [17]. Earlier we have demonstrated that chalcones (open-chain α,β-unsaturated carbonyls) [18] and cyclic chalcone analogues [19,20] possess intrinsic reactivity towards GSH resulting in formation of the expected adducts. Accordingly, thiol reactivity of α,β-unsaturated carbonyl compounds is a basis of one of the biotransformation pathways of this kind of xenobiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced glutathione (GSH) is the most abundant cytosolic thiol playing important role in protection of cells against electrophilesinitiated damages. 17 Earlier we have demonstrated that chalcones (open-chain α,β-unsaturated carbonyls) 18 and cyclic chalcone analogues 19,20 possess intrinsic reactivity towards GSH resulting in formation of the expected adducts. Accordingly, thiol reactivity of α,β-unsaturated carbonyl compounds is a basis of one of the biotransformation pathways of this kind of xenobiotics.…”
Section: Resultsmentioning
confidence: 99%